Comparison of Functional Outcome Between Early and Delayed Internal Fixation Using Volar Locking Plate for Distal Radius Fractures - ZENKE, Yukichi; MORITANI, Shiro; MAEHARA, Takashi; YAMASHITA, Kazuta; SAKAI, Akinori; OSHIGE, Toshihisa (Journal of UOEH, 2015)
The purpose of this study was to assess the effect of timing (Early (E) group vs Delayed (D) group) of internal fixation for distal radius fractures on forearm and wrist function in patients who underwent the surgery. The subjects were one hundred six patients who had extra-articular fractures of the dorsally displaced distal radius and were treated with a volar locking plate. The subjects were divided into two groups: E group (Operation on the day of injury or the next day, n = 76 ; and the D group (Operation at 7 days after injury or later, n = 30). Follow-up examinations conducted at 4, 12, and 48 weeks after surgery included measurements of wrist and forearm ranges of motion (ROM), measurement of grip strength (GS), Disability of the Arm, Shoulder and Hand score (DASH), and complications, retrospectively. The patients in both groups improved significantly with respect to ROM, GS, and DASH. At 4 weeks, the patients in the E group had better forearm motion, At 4 and 12 weeks, those who had undergone early surgery had significantly better wrist motion, GS and DASH. At 48 weeks, there were no differences between the groups in ROM, GS, or DASH. Patients with dorsally displaced extra-articular fractures of the distal radius can expect to have better short-term outcomes with early treatment, open reduction and internal fixation using a volar locking plates.